Disruptive Innovation: Conceptual Foundations, Empirical Evidence, and Research Opportunities in the Digital Age. Issue 3 (22nd April 2018) - Hopp, Christian; Antons, David; Kaminski, Jermain; Oliver Salge, Torsten
Abstract : See virtual issue: Disruptive Innovation